Improvement of Back and Leg Pain after Lumbar Spinal Decompression without Fusion - Geiger, Matthias Florian; Bongartz, Nicola; Blume, Christian; Clusmann, Hans; Müller, Christian Andreas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background To evaluate whether decompression in lumbar spinal stenosis without fusion leads to sufficient improvement of back pain and leg pain and whether re-decompression alone is sufficient for recurrent lumbar spinal stenosis for patients without signs of instability.Material and Methods A successive series of 102 patients with lumbar spinal stenosis (with and without previous lumbar surgery) were treated with decompression alone during a 3-year period. Data on pre- and postoperative back pain and leg pain (numerical rating scale [NRS] scale) were retrospectively collected from questionnaires with a return rate of 65% (n = 66). The complete cohort as well as patients with first-time surgery and re-decompression were analyzed separately. Patients were dichotomized to short-term follow-up (< 100 weeks) and long-term follow-up (> 100 weeks) postsurgery.Results Overall, both back pain (NRS 4.59 postoperative versus 7.89 preoperative; p < 0.0001) and leg pain (NRS 4.09 versus 6.75; p < 0.0001) improved postoperatively. The short-term follow-up subgroup (50%, n = 33) showed a significant reduction in back pain (NRS 4.0 versus 6.88; p < 0.0001) and leg pain (NRS 2.49 versus 6.91: p < 0.0001). Similar results could be observed for the long-term follow-up subgroup (50%, n = 33) with significantly less back pain (NRS 3.94 versus 7.0; p < 0.0001) and leg pain (visual analog scale 3.14 versus 5.39; p < 0.002) postoperatively. Patients with previous decompression surgery benefit significantly regarding back pain (NRS 4.82 versus 7.65; p < 0.0024), especially in the long-term follow-up subgroup (NRS 4.75 versus 7.67; p < 0.0148). There was also a clear trend in favor of leg pain in patients with previous surgery; however, it was not significant.Conclusions Decompression of lumbar spinal stenosis without fusion led to a significant and similar reduction of back pain and leg pain in a short-term and a long-term follow-up group. Patients without previous surgery benefited significantly better, whereas patients with previous decompression benefited regarding back pain, especially for long-term follow-up with a clear trend in favor of leg pain.
Keywords: lumbar spinal stenosis; decompression; re-decompression; outcome; leg and back pain